2016
DOI: 10.5606/archrheumatol.2016.5753
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Tp-e Interval and Tp-e/QT Ratio in Patients With Systemic Sclerosis

Abstract: Objectives: This study aims to investigate ventricular repolarization using T-peak to T-end (Tp-e) intervals and Tp-e/QT ratios in patients with systemic sclerosis (SSc). Patients and methods: Totally 65 patients (8 males, 57 females; mean age 49.8 years; range 20 to 77 years) with SSc and 63 control subjects (8 males, 55 females; mean age 49.3 years; range 20 to 77 years) were enrolled. Tp-e intervals, Tp-e/QT, and Tp-e/corrected QT (QTc) ratios were measured from the 12-lead electrocardiogram. Results: Tp-e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The prolongation of the Tp-e/QTc ratio has been shown in many chronic inflammatory diseases in various studies [29][30][31]. Our study is the first that shows the prolonged Tp-e/QTc ratio in psoriatic arthritis patients.…”
Section: Discussionsupporting
confidence: 62%
“…The prolongation of the Tp-e/QTc ratio has been shown in many chronic inflammatory diseases in various studies [29][30][31]. Our study is the first that shows the prolonged Tp-e/QTc ratio in psoriatic arthritis patients.…”
Section: Discussionsupporting
confidence: 62%
“…This myocardial fibrosis is identified in 50% to 70% of SSc patients, generating prolongation the time required for all ventricular depolarization and repolarization processes to occur. The electrocardiographic sign is represented by the prolonged QTc interval [14,15]. But beside myocardial fibrosis, autonomic dysfunction contributes to QTc prolongation, too [6].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that in dcSSc patients, QTc interval was significantly prolonged than in lcSSc patients [24], but it has not been confirmed by other studies. Another study performed on 65 SSc patients and 63 control subjects showed that the QTc intervals were significantly higher in the former (p < 0.01), without any difference between patients with dcSSc and lcSSc [15]. QTc interval prolongation in SSc patients with late capillaroscopic pattern is associated with a high risk of developing life-threatening ventricular arrhythmias [23].…”
Section: Discussionmentioning
confidence: 99%